ANALYSIS OF THE IMPACT OF FINANCIAL PERFORMANCE ON STOCK PRICES AND COMPANY VALUE AS MODERATION VARIABLES (CASE STUDY ON HEALTHCARE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE) - Florid, Muhamad Irfan; Raflis, Ratnawati (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
Healthcare companies on the Indonesia Stock Exchange (IDX) face fierce competition during the ongoing Covid-19 pandemic, impacting the Jakarta Composite Index (IHSG) despite its stability around 6,000. Pharmaceutical stock prices surged at the pandemic's outset, crucial for investor assessments. This study examines healthcare companies listed on IDX from 2016 to 2020, involving 14 eligible firms. Data analysis employs descriptive statistics and multiple regression analysis, with data analyzed using Eviews 10. Results reveal CR, NPM, TATO, and ROE negatively and significantly affect stock prices, while GPM and EPS have negative but insignificant effects. RC and DER don't significantly impact stock prices, but ROA and PER demonstrate positive, significant effects. Simultaneously, CR, GPM, NPM, RC, TATO, DER, ROA, ROE, EPS, PER, and PBV collectively influence healthcare company stock prices. Company value doesn't moderate CR, RC, TATO, and PER's relationship with stock price but does moderate GPM, NPM, DER, ROA, ROE, EPS, and share prices. Prospective investors should consider factors beyond financial ratios for profitable returns. Keywords: Financial Performance, Stock Prices, Company Value